PERKEMBANGAN KAJIAN TEORITIS TAFSIR DI INDONESIA: TAFSIR AKADEMIS DI PERGURUAN TINGGI AGAMA ISLAM - Zakiar; Hasep Saputra; Sandi Santosa (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This article examines the development of theoretical studies in Qur'anic interpretation in Indonesia, which focus on the dynamics of academic interpretation in Islamic higher education institutions. The study of interpretation in Indonesia has deep historical roots, dating back to the spread of Islam in the Indonesian archipelago and the growth of local intellectual traditions. Since its inception, Qur'anic interpretation has been conducted through various methods and approaches, ranging from traditional to modern and involving the use of supporting disciplines such as hermeneutics, linguistics, semantics, and semiotics. This paper traces the history of interpretation in the Indonesian archipelago, beginning with the spread of Islam by scholars and religious figures, and the emergence of early exegetical works, such as Abd. Rauf as-Singkili's Tarjuman al-Mustafid, and the subsequent emergence of exegetical works in Malay, Javanese, and other local languages. This article also reviews the development of exegesis in Indonesia in the 20th century and beyond, including Howard M. Federspiel's periodization of exegetical works into three generations. Islamic higher education institutions in Indonesia play a vital role in fostering innovation in the methodology, approaches, and models of tafsir studies, thereby enriching the scholarly tradition of tafsir in Indonesia and strengthening the Muslim community's response to the Qur'an as the primary source of Islamic teachings.